Pembinaan direktori dalam talian bidang kepakaran pengajian Islam dan bahasa Arab di institusi pengajian tinggi Malaysia - Ismail, Taufik; Sahrir, Muhammad Sabri; Chik, Abdul Rahman; Nasir, Mohd Shahrizal (Universiti Kebangsaan Malaysia, 2015)

(untitled)
The Islamic and Arabic Studies in Malaysia has undergone a positive transformation. Offered programmes for Islamic and Arabic studies at higher learning institutions in Malaysia have proven that the efforts towards the empowerment of this field are currently on going process. This is further evidence that the number of experts and students who are actively involved in the field of Islamic and Arabic studies is great indeed. In order to ensure that these areas are always relevant and continuously to be strengthened, an expertise directory must be created involving experts in the field of Islamic and Arabic studies. On the other hand, by looking at the benefits to be derived by many parties, especially smart partnership network of teaching and learning, research, publications and so on, such efforts are needed to be intensified towards the construction of expertise directory with the cooperation of all parties. This article aims to gather feedback and suggestions from respondents on the expertise directory in Islamic and Arabic studies in Malaysia. This research is a mix of quantitative and qualitative methodologies that involved 31 respondents from educational institutions from the field of Islamic and Arabic studies. The questionnaires were distributed in an online platform through Google Survey® and were sent to selected respondents via their email, in addition to the posting of survey in social networking sites Facebook®. The questionnaires were also printed and distributed to the respondents who could not be contacted via email correspondence. Based on the findings , the average respondent expressed their positive feedback on the expertise directory and provide further suggestions and comments to improve the online site.